(untitled) (Journal of Asian Development Studies, 2024)
This study explores the relationship between exchange rate volatility and foreign remittances on the economies of SAARC countries over the period 2000 to 2023. With the ongoing debate among policymakers and researchers on this subject, the study employs the Cross-Sectional Autoregressive Distributed Lag (CS-ARDL) model to analyze data from eight SAARC nations. The variables considered include remittances, foreign reserves, trade, foreign direct investment (FDI), political stability, and GDP growth, sourced from the World Development Indicators (WDI), while exchange rate volatility is calculated using the GARCH method. The analysis involves two models. In the first model, remittances serve as the dependent variable, with exchange rate volatility, GDP growth, trade, inflation, and political stability as independent variables. In the second model, exchange rate volatility is the dependent variable, with remittances, GDP growth, trade, inflation, foreign reserves, and FDI as the independent variables. The results indicate both long-run and short-run relationships between exchange rate volatility and foreign remittances in SAARC countries. The findings show that remittances are positively associated with GDP growth and inflation, while exchange rate volatility, trade, and political stability have negative relationships with remittances. Additionally, exchange rate volatility has a positive association with inflation, while GDP growth, remittances, trade, FDI, and foreign reserves exhibit negative associations with exchange rate volatility. Granger causality tests reveal complex bidirectional and unidirectional causal relationships among the variables. These insights offer valuable implications for policymakers aiming to manage exchange rate volatility and enhance remittance inflows in the SAARC region.